Evaluasi Etika Kerja dan Kinerja Teller Bank dalam Memberikan Layanan Kepada Nasabah: Studi Kasus: Bank XXX - Afriyadi Afriyadi; Friska Marlianda Sari; Novi Andriani; Nurul Oktaviani; Raja Amelia Agustinawati; Shandia Saqinah; Tri Utami Miranty; Sarah Nabila Armelia Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze and evaluate the work ethics and performance of tellers at Bank XXX, Tanjung Pinang Branch, and their impact on customer satisfaction and loyalty. The research method used is descriptive research with data collection through questionnaires and interviews. The research population includes all tellers and customers of Bank XXX, with a sample of 11 people selected using purposive sampling technique. The results show that the work ethics and performance of Bank XXX tellers are highly rated by customers, with the majority of respondents giving positive evaluations of teller services. Cooperation between tellers and Customer Service is also considered important in providing integrated and comprehensive services to customers. This research provides valuable insights for banking companies in improving services and maintaining customer loyalty.